Upoštevanje ciljnih uporabnikov pri izdelavi enojezičnega slovarja za tujce - Rozman, Tadeja (Jezik in slovstvo, 2004)
The article addresses the question why a dictionary for foreigners is necessay and what features it ought to have. The findings arise from a thorough knowledge of the field that deals with Slovene as a second/foreign language, a brief analysis of the existing dictionaries of Slovene and English dictionaries for foreigners, and the results of a questionnaire given to participants and teachers of Slovene langugae courses.
Keywords: enojezični slovarji; leksikografija; lexicography; uporabniki